Quantum neurology: a key within physics toward the knowledge of the consciousness? - López Aguilar, Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The contents of this paper are centred on the dialogue between the experimental and positive Sciences and Theology. This dialogue should be based on the principle that both parts have to assume the existence of undemonstrated axioms that are necessary for obtaining their respective valid conclusions. Besides, all interlocutors have to accept the submission of their arguments to the scrutiny of the general scientific method. The relationship between Neurology and Theology is centred on the dichotomy established in the dilemma summarized in whether the conscious acts of the human being are exclusively generated via physical states or are due to an essence within its anthropology that originates the will to do them. Although I do believe in the second branch of this dichotomy, the research of the correlations between physical states of the brain and the consciousness actions are the main goal of my analysis. The fundamentalsof Classical Neurology lie in the assumption that the neuronal system is a complex electronic lattice in such a way that the procedures and developments carried out in it should be similar to those performed in a classical computer. After an analysis of the difficulties of this model in the interpretation of the ontological consciousness properties, I give the basis of the brain study from a Quantum Physics point of view presenting both the known proposal of the Hameroff-Penrose and new proposals based on coherent collective states. The possibility of the survival of quantum coherence of these many-body states to temperatures higher than that of the human body is the main objection posed by the classical neurologists to the availability of Quantum Neurology. The description of two different ways of attaining these many-body coherent states allows us to understand the reasons for this possible survival, this being the main contribution of this work.
Keywords: emergentism in the human soul; brain and self; classical versus quantum neurology; microtubules and tubulins; coherence and collective coherent states; excitonic model of microtubules; biexcitonic model